2016
DOI: 10.3310/hsdr04180
|View full text |Cite
|
Sign up to set email alerts
|

The INCENTIVE study: a mixed-methods evaluation of an innovation in commissioning and delivery of primary dental care compared with traditional dental contracting

Abstract: Godson J, et al. The INCENTIVE study: a mixed-methods evaluation of an innovation in commissioning and delivery of primary dental care compared with traditional dental contracting. Health Serv Deliv Res 2016;4(18). Health Services and Delivery ResearchISSN 2050-4349 (Print) ISSN 2050-4357 (Online) This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/).Editorial contact: nihredit@southampton.ac.ukThe full HS&DR archive is freely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 95 publications
(133 reference statements)
0
18
0
Order By: Relevance
“…Most of the studies (n = 7; 30%) were conducted in the USA, [21][22][23][24][25][26][27] followed (n = 4; 17%) by the UK. 15,[28][29][30] Three studies (13%) from each were conducted in Australia [31][32][33] and The Netherlands [34][35][36] whereas only 2 studies (9%) were reported from the Asian region 37,38 (Table 1). Among the selected articles, the most frequent were on oral cancer (n = 6; 26%), 23,24,27,29,34,36 prosthetic management (n = 6; 26%) 28,35,[38][39][40][41] and prevention of dental caries (n = 4; 17%).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies (n = 7; 30%) were conducted in the USA, [21][22][23][24][25][26][27] followed (n = 4; 17%) by the UK. 15,[28][29][30] Three studies (13%) from each were conducted in Australia [31][32][33] and The Netherlands [34][35][36] whereas only 2 studies (9%) were reported from the Asian region 37,38 (Table 1). Among the selected articles, the most frequent were on oral cancer (n = 6; 26%), 23,24,27,29,34,36 prosthetic management (n = 6; 26%) 28,35,[38][39][40][41] and prevention of dental caries (n = 4; 17%).…”
Section: Methodsmentioning
confidence: 99%
“…values from the patients using the time trade-off method. The Euro-Qol-EQ-5D-3L questionnaire was used by four studies, 28,30,36,37 and one study 33 used the Child Health Utility 9D (CHU-9D) questionnaire with utility values based on proxy population weights. One study 35 converted patients' SF-36 scores to QALYs using the SF-6D excel scoring programme (Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the 1980s and 1990s, Reisine, Bailit, Sheiham, Croog, Roseenberg and many others continued the trials. Today, there are a vast number of clinically verified indices, and each day they are improving postures and creating new indexes [7,8,9].…”
Section: Introductionmentioning
confidence: 99%